4D printing of shape memory polybutylene succinate/polylactic acid (PBS/PLA) and its potential applications. (1st January 2022) - Lin, Cheng; Liu, Liwu; Liu, Yanju; Leng, Jinsong
Graphic abstract: Highlights: 4D printed PBS/PLA filament was first developed. The graphene oxide (GO) functionalized shape memory PBS/PLA porous scaffold can be actuated by near-infrared (NIR) laser, enabling dynamic, remote, and accurate control of the 4D transformation process. Various complex architectures (e.g. starfish, aneurysm model) were high-quality printed using 4D printing PBS/PLA filament. 4D printing PBS/PLA filament with outstanding shape memory performance exhibited a promising prospect in the biomedical field. Abstract: 4D printing adds time as the fourth dimension to 3D printing, which has been actively explored in the biomedical field to develop patient-specific implants due to the ease of manufacturing complex architectures and the capability of dynamic transformations. However, the 4D printing filament used for fused deposition modeling (FDM) is quite limited. Here, 4D printing shape memory polybutylene succinate/polylactic acid (PBS/PLA) composite filament is prepared. The mechanical properties, surface morphology, and shape memory performances of the printed specimens are investigated. Besides, graphene oxide functionalized PBS/PLA shows attractive photothermal properties under near-infrared (NIR) irradiation, and a dynamic, remote, and accurate controlled 4D transformation of a porous scaffold is exhibited. As the first demonstration of 4D printing filament of PBS/PLA for FDM, this work shows its promising application prospects in tissue engineering, photothermal therapy, etc. Additionally, NIR-triggered 4D transformation solves the problem that the conventional thermal-trigger transformation process is difficult to control.